A high-capacity lithium iron phosphate positive electrode material and preparation method thereof
By combining perovskite structural ion conductors with lithium iron phosphate positive electrode materials, and using the combination of rare earths and transition metal elements, the problems of poor conductivity and slow lithium ion migration rate of lithium iron phosphate positive electrode materials are solved, and the high capacity and excellent electrochemical performance of the material are achieved.
Patent Information
- Application Number
- CN202411752216.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-02
AI Technical Summary
Lithium iron phosphate positive electrode material has problems such as poor conductivity, slow lithium ion migration rate and small actual capacity, which limits the improvement of its electrochemical performance.
Perovskite structured ion conductors are used to combine with lithium iron phosphate positive electrode material, and the combination of rare earths and transition metal elements is used to form materials with high ionic conductivity and lithium ion storage capacity, improving the diffusion efficiency and electron transfer rate of lithium ions.
The circulation performance, rate performance and capacity retention of lithium iron phosphate positive electrode material are significantly improved, and the thermal stability and electrochemical properties of the material are enhanced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a high-capacity lithium iron phosphate positive electrode material and a preparation method thereof. Background Art
[0002] In recent years, with the rapid development of new energy vehicles and energy storage, people's demand for lithium-ion batteries has also increased. As one of the important components of lithium-ion batteries, positive electrode materials are the key factors that determine their comprehensive performance. The specific capacity, structural stability and electrical properties of positive electrode materials can directly affect the overall performance of lithium-ion batteries.
[0003] Among them, lithium iron phosphate, as a positive electrode material for lithium-ion batteries, is widely used because of its advantages such as good safety performance, long service life and low cost. However, lithium iron phosphate positive electrode materials are limited by their own crystal structure, and have problems such as poor conductivity, slow lithium ion migration rate and small actual capacity, which greatly limit the improvement of their electrochemical performance. At present, the most commonly used modification method is to improve lithium iron phosphate materials through carbon coating. Carbon is a good electronic conductor and can significantly improve the electronic conductivity of the material, thereby improving its electrochemical performance. However, carbon is not a good conductor of lithium ions. When the diffusion rate of lithium ions cannot match the transmission rate of electrons that need to be transferred, it will affect the transmission efficiency of electrons, which is not conducive to the improvement of the overall electrochemical performance, and may cause the material capacity to decline faster. Summary of the invention
[0004] The purpose of the present invention is to provide a high-capacity lithium iron phosphate positive electrode material and a preparation method thereof, so as to solve the problems of poor conductivity, small capacity and poor cycle performance of the lithium iron phosphate positive electrode material.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] In a first aspect, the present invention provides a high-capacity lithium iron phosphate positive electrode material, wherein the lithium iron phosphate positive electrode material is composited with a perovskite structure ion conductor; the structural formula of the perovskite structure ion conductor is A x B 1-x O 2-δ , and 0.2≤x≤0.8, 0<δ<2; in the structural formula, A is a rare earth element, and the rare earth element is any one of lanthanum, cerium, praseodymium, neodymium, samarium and gadolinium; B is a transition metal element, and the transition metal element is any one of chromium, manganese, iron, cobalt, nickel, copper and zinc.
[0007] By adopting the above technical solution, the lithium iron phosphate positive electrode material of the present invention is also compounded with a perovskite structure ion conductor, wherein "δ" represents a non-stoichiometric ratio, that is, it indicates that there are certain oxygen vacancies in the structure, specifically, 0<δ<2. The ion conductor material has high ionic conductivity and lithium ion storage capacity. During the charging and discharging process of the lithium ion battery, it can accelerate the diffusion efficiency of lithium ions and achieve matching of the transmission rate of lithium ions and free electrons, thereby enhancing the material's cycle performance and self-capacity. In addition, the ion conductor contains rare earth atoms, which can provide additional migration channels for lithium ions, accelerate the diffusion rate of lithium ions, and improve the thermal stability of the material, thereby improving the rate performance and electrochemical performance of the positive electrode material, and can show a more excellent capacity retention rate.
[0008] At the same time, the ion conductor material is doped with transition metal atoms, which can provide additional electron conduction paths for the lithium iron phosphate cathode material, thereby improving the overall electronic conductivity of the material and matching the lithium ion diffusion rate. Transition metal doping can also introduce new active sites for the lithium iron phosphate cathode material, enhancing the actual capacity of the lithium iron phosphate cathode material.
[0009] The ion conductor obtained by combining rare earth atoms and transition metal atoms has a perovskite structure. The ion conductor with a perovskite structure can provide a large number of equivalent sites for the lattice of the lithium iron phosphate positive electrode material. Lithium ions can occupy these equivalent sites on the ion conductor and can move freely, thereby increasing the diffusion channel of lithium ions, shortening the diffusion path of lithium ions, and significantly improving the transmission performance of lithium ions. It not only increases the storage capacity of lithium ions and improves the capacity of the positive electrode material, but also enhances the electrochemical performance of the lithium iron phosphate positive electrode material.
[0010] Preferably, the raw materials of the perovskite structure ion conductor include rare earth nitrate and transition metal nitrate in a molar ratio of (0.25-0.8): (0.2-0.8).
[0011] More preferably, the rare earth nitrate includes one of lanthanum nitrate, cerium nitrate, praseodymium nitrate, neodymium nitrate, samarium nitrate hexahydrate and gadolinium nitrate hexahydrate.
[0012] More preferably, the transition metal nitrate includes one of chromium nitrate nonahydrate, manganese nitrate tetrahydrate, iron nitrate, cobalt nitrate hexahydrate, nickel nitrate, copper nitrate and zinc nitrate.
[0013] Preferably, the perovskite structured ion conductor is prepared according to the following method: rare earth nitrate and transition metal nitrate are added to deionized water, stirred and dissolved at 40-50°C, then a complexing agent is added, stirred and mixed for 30-60 minutes, then the temperature is increased to 80-85°C, and the stirring reaction is continued for 12-15 hours to obtain a gel premix, which is then dried, sintered and ground to obtain a perovskite structured ion conductor.
[0014] Preferably, the complexing agent comprises one or a combination of citric acid, ethylenediaminetetraacetic acid, polyvinylpyrrolidone and oxalic acid.
[0015] Preferably, the added amount of the complexing agent is 30-50% of the total mass of the rare earth nitrate and the transition metal nitrate.
[0016] Preferably, the sintering temperature is 1100-1200°C.
[0017] By adopting the above technical scheme, under the action of the complexing agent, rare earth nitrate and transition metal nitrate are dissolved in water, and a sol-gel reaction is carried out. After high-temperature sintering, an ion conductor with a perovskite structure is obtained. The ion conductor contains both rare earth elements and transition metal elements, so that the lithium ion diffusion rate and the free electron transmission rate of the lithium iron phosphate positive electrode material can be coordinated to achieve unity between the two, and jointly improve the conductivity, rate performance and capacity of the lithium iron phosphate positive electrode material.
[0018] In a second aspect, the present invention provides a method for preparing a high-capacity lithium iron phosphate positive electrode material, comprising the following process steps:
[0019] S1. adding a phosphorus source, an iron source and a lithium source to deionized water to obtain a mixed solution;
[0020] S2. Add the tannin composite conductive hydrogel to deionized water, add the mixed solution after uniform dispersion, stir and mix, then add the perovskite structure ion conductor, increase the temperature to 50-60° C., stir and react for 4-6 hours to obtain a mixed slurry;
[0021] S3. After the mixed rubber material is spray-dried, it is sintered at 700-850° C. for 6-8 hours in a nitrogen atmosphere, and finally ground to obtain a high-capacity lithium iron phosphate positive electrode material.
[0022] Preferably, the molar ratio of the perovskite structure ion conductor to the phosphorus source is (0.4-0.5):1.
[0023] Preferably, the added amount of the tannin composite conductive hydrogel is 10-20% of the total mass of the phosphorus source, the iron source and the lithium source.
[0024] Preferably, the molar ratio of the phosphorus source, the iron source and the lithium source is 1:(0.9-1.05):(0.95-1.1).
[0025] Preferably, the phosphorus source includes a combination of one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, lithium hydrogen phosphate, lithium dihydrogen phosphate, sodium phosphate and potassium phosphate.
[0026] Preferably, the iron source comprises a combination of one or more of ferric nitrate, ferric sulfate, ferric carbonate, ferric chloride, ferrous nitrate and ferric oxide.
[0027] Preferably, the lithium source includes one or a combination of lithium hydroxide, lithium acetate, lithium carbonate, lithium oxalate, lithium chloride and lithium acetate.
[0028] In the preparation process of the lithium iron phosphate positive electrode material of the present invention, a tannin composite conductive hydrogel is also added. By adopting the above technical scheme, the introduction of the conductive hydrogel into the mixed solution helps to form a continuous conductive network between the lithium iron phosphate particles, and can help to form a three-dimensional space structure. After the composite perovskite structured ion conductor, the lithium iron phosphate positive electrode material is sintered, so that the carbon layer as a good electronic conductor and the perovskite structured ion conductor particles as a good ion conductor are jointly coated on the surface of the lithium iron phosphate positive electrode material, which jointly improve the diffusion rate of lithium ions and the free electron transmission rate. In addition, the construction of the three-dimensional space conductive network can increase the capacity of the positive electrode material, and provide a large number of transmission paths, thereby improving the rate performance and cycle performance of the positive electrode material.
[0029] Moreover, the slurry formed by adding the conductive hydrogel is more conducive to the dispersion of the perovskite structure ion conductor in the system. The conductive hydrogel of the present invention is also compounded with tannin. The large amount of ortho-dihydroxyphenol groups contained in the tannin can attract and complex the metal ions in the perovskite structure ion conductor, thereby improving the binding force between the lithium iron phosphate positive electrode material and the ion conductor. After sintering, the ion conductor can be tightly connected to the lithium iron phosphate positive electrode material, and is not easy to fall off during the charge and discharge cycle, thereby improving the cycle performance and service life of the lithium iron phosphate positive electrode material.
[0030] Preferably, the raw materials of the tannin composite conductive hydrogel include polyvinyl alcohol, sodium alginate and condensed tannin in a mass ratio of 1: (0.4-0.6): (0.2-0.3).
[0031] Preferably, the tannin composite conductive hydrogel is prepared according to the following method: sodium chloride and sodium alginate are added to deionized water, stirred and dissolved at 40-50°C, and then allowed to stand at room temperature for 10-12 hours, then polyvinyl alcohol and condensed tannin are added, stirred and reacted at 90-100°C for 3-5 hours, and after the reaction is completed, the reaction is frozen at -25--20°C for 10-12 hours, and the tannin composite conductive hydrogel is obtained by grinding and thawing.
[0032] By adopting the above technical solution, the tannin of the present invention adopts condensed tannin, which has more o-dihydroxyphenol groups than hydrolyzed tannin, and can better connect the lithium iron phosphate positive electrode material and the perovskite structure ion conductor, thereby improving the binding force between the two during compounding. At the same time, the conductive hydrogel is filled between the lithium iron phosphate positive electrode materials, forming a continuous conductive network, which can construct a three-dimensional carbon layer after sintering, increase the movement path of free electrons and lithium ions, and improve the capacity and conductivity of the material.
[0033] Beneficial effects of the present invention:
[0034] 1. The lithium iron phosphate positive electrode material of the present invention is composited with a perovskite structure ion conductor. The perovskite structure ion conductor can provide more movement space for lithium ions. Its higher ion conductivity and lithium ion storage capacity can improve the lithium ion diffusion rate and capacity of the composite lithium iron phosphate positive electrode material. The rare earth atoms contained in the ion conductor can provide additional migration channels for lithium ions, and the transition metal atoms can provide additional electron conduction paths, thereby achieving matching of the transmission rates of lithium ions and free electrons and improving the cycle performance of the positive electrode material.
[0035] 2. Tannin composite conductive hydrogel is added to the lithium iron phosphate positive electrode material during the preparation process. The conductive hydrogel can form a continuous conductive network between the lithium iron phosphate positive electrode material particles, and a large number of o-dihydroxyphenol groups on the composite tannin molecules can attract and complex the perovskite structure ion conductor, thereby improving the dispersibility and binding force between the lithium iron phosphate particles and the perovskite structure ion conductor. The composite material is not easy to separate during the charge and discharge cycle; after sintering, the ion conductor and the electronic conductor can be co-coated on the lithium iron phosphate positive electrode material, thereby further improving the rate performance and cycle performance of the material. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Preparation Example
[0038] Preparation Example 1 Perovskite structure ion conductor
[0039] Preparation Example 1-1, a perovskite structure ion conductor is prepared according to the following method:
[0040] 0.6 mol of cerium nitrate and 0.4 mol of zinc nitrate were added to 500 mL of deionized water, stirred and dissolved at 45 °C, and then 100 g of ethylenediaminetetraacetic acid was added and stirred for 40 min. The temperature was then raised to 80 °C and the reaction was continued with stirring for 12 h to obtain a gel premix. The perovskite structure ion conductor Ce was then obtained through drying, sintering and grinding. 0.6 Zn 0.4 O 2-δ (0<δ<2), where the sintering temperature is 1200℃.
[0041] Preparation Example 1-2, a perovskite structure ion conductor, which is different from Preparation Example 1-1 only in that the molar ratio of cerium nitrate to zinc nitrate is 0.25:0.8, and the perovskite structure ion conductor Ce is obtained. 0.2 Zn 0.8 O 2-δ .
[0042] Preparation Example 1-3, a perovskite structure ion conductor, which is different from Preparation Example 1-1 only in that the molar ratio of cerium nitrate to zinc nitrate is 0.8:0.2, and the perovskite structure ion conductor Ce is obtained. 0.8 Zn 0.2 O 2-δ .
[0043] Preparation Example 1-4, a perovskite structure ion conductor, which differs from Preparation Example 1-1 only in that cerium nitrate is replaced by an equal mole of praseodymium nitrate to obtain a perovskite structure ion conductor Pr 0.8 Zn 0.2 O 2-δ .
[0044] Preparation Example 1-5, a perovskite structure ion conductor, which differs from Preparation Example 1-1 only in that cerium nitrate is replaced by an equal mole of neodymium nitrate and zinc nitrate is replaced by an equal mole of nickel nitrate to obtain a perovskite structure ion conductor Nd 0.8 Ni 0.2 O 2-δ .
[0045] Preparation Example 1-6, a perovskite structure ion conductor, which is different from Preparation Example 1-1 only in that the molar ratio of cerium nitrate to zinc nitrate is 0.9:0.1, and the perovskite structure ion conductor Ce is obtained. 0.9 Zn 0.1 O 2-δ .
[0046] Preparation Example 1-7, a perovskite structure ion conductor, which is different from Preparation Example 1-1 only in that the molar ratio of cerium nitrate to zinc nitrate is 0.1:0.9, and the perovskite structure ion conductor Ce is obtained. 0.1 Zn 0.9 O 2-δ .
[0047] Preparation Example 1-8, an ion conductor, is prepared according to the following method:
[0048] Add 1 mol of cerium nitrate to 500 mL of deionized water, stir and dissolve at 45°C, then add 90 g of ethylenediaminetetraacetic acid, stir and mix for 40 minutes, then increase the temperature to 80°C, continue stirring and reacting for 12 hours to obtain a gel premix, and then dry, sinter and grind to obtain the ion conductor CeO2, where the sintering temperature is 1200°C.
[0049] Preparation Example 1-9, an ion conductor, is different from Preparation Example 1-8 only in that cerium nitrate is replaced by an equal mole of zinc nitrate to obtain an ion conductor ZnO.
[0050] Preparation Example 1-10, a perovskite structure ion conductor, which differs from Preparation Example 1-1 only in that cerium nitrate is replaced by an equal mole of strontium nitrate to obtain a perovskite structure ion conductor Sr 0.8 Zn 0.2 O 2-δ .
[0051] Preparation Example 1-11, a perovskite structure ion conductor, which differs from Preparation Example 1-1 only in that zinc nitrate is replaced by an equal molar amount of magnesium nitrate to obtain a perovskite structure ion conductor Ce 0.8 Mg 0.2 O 2-δ .
[0052] Preparation Example 2 Tannin composite conductive hydrogel
[0053] Preparation Example 2-1, a tannin composite conductive hydrogel, is prepared according to the following method:
[0054] Add 3g of sodium chloride and 5g of sodium alginate to 250mL of deionized water, stir to dissolve at 40°C, and let stand at room temperature for 12h. Then add 10g of polyvinyl alcohol (average weight-average molecular weight of 20,000) and 2.5g of condensed tannin, stir and react at 100°C for 4h. After the reaction, freeze at -20°C for 12h, and grind and thaw to obtain tannin composite conductive hydrogel.
[0055] Preparation Example 2-2, a tannin composite conductive hydrogel, is different from Preparation Example 2-1 only in that the added amount of sodium alginate is 6 g and the added amount of condensed tannin is 2 g.
[0056] Preparation Example 2-3, a tannin composite conductive hydrogel, is different from Preparation Example 2-1 only in that the added amount of sodium alginate is 4 g and the added amount of condensed tannin is 3 g.
[0057] Preparation Example 2-4, a tannin composite conductive hydrogel, is different from Preparation Example 2-1 only in that the added amount of condensed tannin is 1 g.
[0058] Preparation Example 2-5, a tannin composite conductive hydrogel, is different from Preparation Example 2-1 only in that the added amount of condensed tannin is 4 g.
[0059] Preparation Example 2-6, a tannin composite conductive hydrogel, is different from Preparation Example 2-1 only in that an equal amount of hydrolyzed tannin (tannic acid) is used to replace the condensed tannin.
[0060] Preparation Example 2-7, a conductive hydrogel, is prepared according to the following method:
[0061] Add 3g of sodium chloride and 5g of sodium alginate to 250mL of deionized water, stir and dissolve at 40°C, and let stand at room temperature for 12h. Then add 10g of polyvinyl alcohol (average weight-average molecular weight is 20,000) and stir to react at 100°C for 4h. After the reaction, freeze it at -20°C for 12h. After grinding and thawing, the tannin composite conductive hydrogel is obtained.
[0062] Example
[0063] Example 1: A high-capacity lithium iron phosphate positive electrode material is prepared according to the following process steps:
[0064] S1. ammonium dihydrogen phosphate, ferric sulfate and lithium hydroxide were added to deionized water to obtain a mixed solution, wherein the amount of ammonium dihydrogen phosphate added was 1 mol, the molar ratio of ammonium dihydrogen phosphate, ferric sulfate and lithium hydroxide was 1:1:1, and the solid content of the mixed solution was 50%;
[0065] S2. 80 g of the tannin composite conductive hydrogel prepared in Preparation Example 2-1 was added to deionized water with a solid content of 20%, and the mixture was evenly dispersed and stirred, and then 0.45 mol of the perovskite structure ion conductor prepared in Preparation Example 1-1 was added, the temperature was raised to 60 ° C, and the reaction was stirred for 5 h to obtain a mixed slurry;
[0066] S3. After the mixed rubber material is spray-dried, it is sintered at 800°C for 6 hours in a nitrogen atmosphere and finally ground to obtain a high-capacity lithium iron phosphate positive electrode material.
[0067] Example 2, a high-capacity lithium iron phosphate positive electrode material, differs from Example 1 only in that the molar ratio of ammonium dihydrogen phosphate, ferric sulfate and lithium hydroxide is 1:0.9:0.95; the tannin composite conductive hydrogel prepared in Preparation Example 2-2 is used to replace the tannin composite conductive hydrogel prepared in Preparation Example 2-1; the perovskite structure ion conductor of Preparation Example 1-1 is replaced with an equal molar perovskite structure ion conductor prepared in Preparation Example 1-2.
[0068] Example 3, a high-capacity lithium iron phosphate positive electrode material, which differs from Example 1 only in that the molar ratio of ammonium dihydrogen phosphate, ferric sulfate and lithium hydroxide is 1:1.05:1.1; the tannin composite conductive hydrogel prepared in Preparation Example 2-3 is used to replace the tannin composite conductive hydrogel prepared in Preparation Example 2-1; the perovskite structured ion conductor of Preparation Example 1-1 is replaced with an equal molar perovskite structured ion conductor prepared in Preparation Example 1-3.
[0069] Example 4, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the added amount of the tannin composite conductive hydrogel prepared in Preparation Example 2-1 is 54 g.
[0070] Example 5, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the added amount of the tannin composite conductive hydrogel prepared in Preparation Example 2-1 is 105 g.
[0071] Example 6, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the added amount of the perovskite structure ion conductor of Preparation Example 1-1 is 0.4 mol.
[0072] Example 7, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the added amount of the perovskite structure ion conductor of Preparation Example 1-1 is 0.5 mol.
[0073] Example 8, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the perovskite structure ion conductor of Preparation Example 1-1 is replaced by an equimolar perovskite structure ion conductor prepared in Preparation Example 1-4.
[0074] Example 9, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the perovskite structure ion conductor of Preparation Example 1-1 is replaced by an equimolar perovskite structure ion conductor prepared in Preparation Example 1-5.
[0075] Example 10, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the tannin composite conductive hydrogel prepared in Preparation Example 2-1 is replaced by an equal amount of the tannin composite conductive hydrogel prepared in Preparation Example 2-4.
[0076] Example 11, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the tannin composite conductive hydrogel prepared in Preparation Example 2-1 is replaced by an equal amount of the tannin composite conductive hydrogel prepared in Preparation Example 2-5.
[0077] Example 12, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the tannin composite conductive hydrogel prepared in Preparation Example 2-1 is replaced by an equal amount of the tannin composite conductive hydrogel prepared in Preparation Example 2-6.
[0078] Example 13, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the added amount of the perovskite structure ion conductor of Preparation Example 1-1 is 0.3 mol.
[0079] Example 14, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the added amount of the perovskite structure ion conductor of Preparation Example 1-1 is 0.6 mol.
[0080] Example 15, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the added amount of the tannin composite conductive hydrogel prepared in Preparation Example 2-1 is 25 g.
[0081] Example 16, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the added amount of the tannin composite conductive hydrogel prepared in Preparation Example 2-1 is 135 g.
[0082] Comparative Example
[0083] Comparative Example 1, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the perovskite structure ion conductor of Preparation Example 1-1 is replaced by an equimolar perovskite structure ion conductor prepared in Preparation Example 1-6.
[0084] Comparative Example 2, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the perovskite structure ion conductor of Preparation Example 1-1 is replaced by an equimolar perovskite structure ion conductor prepared in Preparation Example 1-7.
[0085] Comparative Example 3, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the perovskite structure ion conductor of Preparation Example 1-1 is replaced by an ion conductor prepared in Preparation Example 1-8 in an equal molar amount.
[0086] Comparative Example 4, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the perovskite structure ion conductor of Preparation Example 1-1 is replaced by an ion conductor prepared in Preparation Example 1-9 in an equal molar amount.
[0087] Comparative Example 5, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the perovskite structure ion conductor of Preparation Example 1-1 is replaced by an equimolar perovskite structure ion conductor prepared in Preparation Example 1-10.
[0088] Comparative Example 6, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the perovskite structured ion conductor of Preparation Example 1-1 is replaced by an equimolar perovskite structured ion conductor prepared in Preparation Example 1-11.
[0089] Comparative Example 7, a high-capacity lithium iron phosphate positive electrode material, differs from Example 1 only in that the tannin composite conductive hydrogel prepared in Preparation Example 2-1 is replaced by an equal amount of the tannin composite conductive hydrogel prepared in Preparation Example 2-7.
[0090] Comparative Example 8, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the perovskite structure ion conductor prepared in Preparation Example 1-1 is not added.
[0091] Comparative Example 9, a high-capacity lithium iron phosphate positive electrode material, is different from Example 1 only in that the tannin composite conductive hydrogel prepared in Preparation Example 2-1 is not added.
[0092] Performance testing
[0093] Sample preparation:
[0094] The lithium iron phosphate positive electrode material obtained in the embodiment and the comparative example was mixed with a conductive agent (conductive carbon black) and a binder (polyvinylidene fluoride) in a mass ratio of 8:1:1, and 0.05 g / mL of N-methyl-2-pyrrolidone was added to dilute the slurry, and the mixture was ground and coated on an aluminum foil, and dried at 80°C for 24 h to obtain a positive electrode sheet. Under a nitrogen atmosphere, a 2032-type button battery was prepared using a lithium sheet as a negative electrode material, a polypropylene microporous membrane as a separator, and 1 mol / L LiPF6 as an electrolyte.
[0095] 1. Specific capacity test: In the voltage range of 2.0~3.8V, at a constant temperature of 25℃, test the first discharge capacity of the sample battery at 1C and 10C rates respectively;
[0096] 2. Cycle performance test: In the voltage range of 2.0 ~ 3.8V, 25℃ constant temperature conditions and 1C rate, the sample battery is charged and discharged cycle tested, and the capacity retention rate of the sample battery after 500 cycle tests is calculated.
[0097] The above test results are shown in Table 1:
[0098]
[0099] According to Table 1, combined with Example 1, Example 2 to Example 9, it can be seen that there is no significant difference in the discharge capacity at different rates and the cycle capacity retention rate of the material between Example 2 to Example 9 and Example 1, indicating that there is no significant difference in the capacity and cycle performance of Example 2 to Example 9 compared with Example 1. The reason is that the changes in Example 2 to Example 7 compared with Example 1 are only in the change of the raw materials and the raw material ratio within the required range, which has little effect on the final battery performance; compared with Example 1, Examples 8 and Example 9 change the types of rare earth elements and transition metal elements, indicating that different rare earth elements and transition metal elements can improve the capacity and cycle performance of the material to a certain extent.
[0100] Combining Example 1, Example 10, Example 11 and Comparative Example 7, it can be seen that the discharge capacity and capacity retention rate of Example 10, Example 11 and Comparative Example 7 are all reduced compared with Example 1, and the reduction in Example 10 and Comparative Example 7 is more obvious. The reason is that the content of tannin in the tannin composite conductive hydrogel used in Example 10 is reduced, and the attraction to the perovskite structure ion conductor in the system is reduced, resulting in a decrease in the binding force between the lithium iron phosphate particles and the ion conductor, resulting in the ion conductor falling off during the cycle, and the capacity retention rate is reduced. In Comparative Example 7, no tannin composite conductive hydrogel is used, and the cycle performance of the material is more significantly reduced. In Example 11, the tannin content is increased, which will hinder the uniform dispersion of the ion conductor in the system, resulting in a slight decrease in the performance of the material.
[0101] Combining Example 1 and Example 12, it can be seen that the discharge capacity and capacity retention rate of Example 12 are lower than those of Example 1. The reason is that hydrolyzed tannin is used in Example 12, and the number of o-dihydroxyphenol groups in hydrolyzed tannin is significantly reduced compared to condensed tannin, resulting in a decrease in the attraction and complexation of perovskite structured ion conductors, a decrease in the binding force between the ion conductor and the lithium iron phosphate particles, and a decrease in the material cycle performance.
[0102] Combining Example 1, Example 13, Example 14 and Comparative Example 8, it can be seen that the discharge capacity and capacity retention rate of Example 13, Example 14 and Comparative Example 8 are all reduced compared with Example 1, and the reduction in Comparative Example 8 is more obvious. The reason is that the number of ion conductors is changed in Example 13, Example 14 and Comparative Example 8. Specifically, the amount of ion conductors is reduced in Example 13, the storage capacity of lithium ions is reduced, and the diffusion rate of lithium ions in the obtained lithium iron phosphate positive electrode material is reduced. The carbon layer formed by the tannin composite conductive hydrogel will increase the transmission rate of electrons, resulting in a mismatch between the transmission rates of the two, and then resulting in a decrease in the capacity and cycle performance of the material; there is no composite perovskite structure ion conductor in Comparative Example 8, and the performance of the material is more significantly reduced. In Example 14, the amount of ion conductor added is increased, which will also lead to system imbalance and a decrease in the cycle performance of the material.
[0103] Combining Example 1, Example 15, Example 16 and Comparative Example 9, it can be seen that the discharge capacity and capacity retention rate of Example 15, Example 16 and Comparative Example 9 are all reduced compared with Example 1, and the reduction in Comparative Example 9 is more obvious. The reason is that the addition amount of tannin composite conductive hydrogel is changed in Example 15, Example 16 and Comparative Example 9. Specifically, the addition amount of tannin composite conductive hydrogel is reduced in Example 15. In addition to reducing the binding force between lithium iron phosphate particles and perovskite structure ion conductors, it also leads to uneven sintering to form an electronic conductor carbon layer, and the electron transmission rate is affected. In Comparative Example 9, no tannin composite conductive hydrogel is added, and the performance degradation is more obvious. In Example 16, the addition amount of tannin composite conductive hydrogel is increased, which will hinder the dispersibility of perovskite structure ion conductors in the system, resulting in a decrease in material performance.
[0104] In combination with Example 1 and Comparative Examples 1 to 6, it can be seen that the discharge capacity and capacity retention rate of Comparative Examples 1 to 6 are significantly reduced compared to Example 1. The reason is that Comparative Examples 1 and 2 change the ratio of rare earth elements and transition metal elements. The proportion of transition metal atoms in Comparative Example 1 is small, so the electron conduction path in the material is reduced, affecting the conductivity of the material. The proportion of rare earth elements in Comparative Example 2 is small, and the ion conduction efficiency of the perovskite structure ion conductor is poor, and the storage capacity of lithium ions is also reduced. Comparative Examples 5 and 6, while maintaining the perovskite structure, replace the rare earth elements and transition metal elements with alkaline earth metals, resulting in a more obvious decline in material performance. Comparative Examples 3 and 4 not only lack rare earth elements or transition metal elements, but also lose their perovskite structure, resulting in a reduction in the equivalent active sites for lithium ions in the positive electrode material, a decrease in the diffusion performance of lithium ions, and a significant decrease in the capacity and cycle performance of the material.
[0105] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0106] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-capacity lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material is compounded with a perovskite structure ion conductor; the structural formula of the perovskite structure ion conductor is A x B 1-x O 2-δ , and 0.2≤x≤0.8, 0<δ<2; in the structural formula, A is a rare earth element, and the rare earth element is any one of lanthanum, cerium, praseodymium, neodymium, samarium and gadolinium; B is a transition metal element, and the transition metal element is any one of chromium, manganese, iron, cobalt, nickel, copper and zinc.
2. The high-capacity lithium iron phosphate positive electrode material according to claim 1, characterized in that: The raw materials of the perovskite structure ion conductor include rare earth nitrate and transition metal nitrate in a molar ratio of (0.25-0.8): (0.2-0.8).
3. The high-capacity lithium iron phosphate positive electrode material according to claim 2, characterized in that: The perovskite structure ion conductor is prepared according to the following method: rare earth nitrate and transition metal nitrate are added to deionized water, stirred and dissolved at 40-50° C., then a complexing agent is added, stirred and mixed for 30-60 minutes, then the temperature is increased to 80-85° C., and the stirring reaction is continued for 12-15 hours to obtain a gel premix, which is then dried, sintered and ground to obtain a perovskite structure ion conductor.
4. The high-capacity lithium iron phosphate positive electrode material according to claim 3, characterized in that: The complexing agent includes one or a combination of citric acid, ethylenediaminetetraacetic acid, polyvinyl pyrrolidone and oxalic acid.
5. A method for preparing a high-capacity lithium iron phosphate positive electrode material according to any one of claims 1 to 4, characterized in that: The process steps include: S1. adding a phosphorus source, an iron source and a lithium source to deionized water to obtain a mixed solution; S2. Add the tannin composite conductive hydrogel to deionized water, add the mixed solution after uniform dispersion, stir and mix, then add the perovskite structure ion conductor, increase the temperature to 50-60° C., stir and react for 4-6 hours to obtain a mixed slurry; S3. After the mixed rubber material is spray dried, it is sintered at 700-850° C. for 6-8 hours in a nitrogen atmosphere, and finally ground to obtain a high-capacity lithium iron phosphate positive electrode material; The raw materials of the tannin composite conductive hydrogel include polyvinyl alcohol, sodium alginate and condensed tannin in a mass ratio of 1: (0.4-0.6): (0.2-0.3).
6. The method for preparing a high-capacity lithium iron phosphate positive electrode material according to claim 5, characterized in that: The molar ratio of the perovskite structure ion conductor to the phosphorus source is (0.4-0.5):
1.
7. The method for preparing a high-capacity lithium iron phosphate positive electrode material according to claim 5, characterized in that: The tannin composite conductive hydrogel is prepared according to the following method: sodium chloride and sodium alginate are added to deionized water, stirred and dissolved at 40-50°C, and then allowed to stand at room temperature for 10-12 hours, then polyvinyl alcohol and condensed tannin are added, stirred and reacted at 90-100°C for 3-5 hours, and after the reaction is completed, the mixture is frozen at -25--20°C for 10-12 hours, and the tannin composite conductive hydrogel is obtained by grinding and thawing.
8. The method for preparing a high-capacity lithium iron phosphate positive electrode material according to claim 5, characterized in that: The added amount of the tannin composite conductive hydrogel is 10-20% of the total mass of the phosphorus source, the iron source and the lithium source.
9. The method for preparing a high-capacity lithium iron phosphate positive electrode material according to claim 5, characterized in that: The molar ratio of the phosphorus source, the iron source and the lithium source is 1:(0.9-1.05):(0.95-1.1).
Citation Information
Patent Citations
Positive electrode material for lithium ion battery, and preparation method thereof
CN111682200A
Method for improving multiplying power and prolonging service life of high-compaction pole piece
CN118610406A